Comparative study on sustainable living campaign for Malaysia by using motion graphics - Jamil, Muhammad Faisal; Hairul Anuar, Inda Murni; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
Malaysia is currently facing a serious environmental issue caused by the increasing volume of household waste. This problem stems not only from infrastructural challenges but also from public behaviour and a general lack of awareness about the environmental impact of daily consumption habits. Although the government and NGOs have launched various initiatives like “No Plastic Bag Day” and green campaigns, public participation remains low. This study explores how motion graphics can be used to promote sustainable living and influence positive behavioural change. By comparing ten video campaigns from Malaysia with ten from Japan, the research examines how visual elements such as typography, imagery, animation, and sound are used to convey environmental messages. Using qualitative content analysis, the study finds that Malaysian campaigns tend to prefer clean, sans-serif fonts, 2D animation, and consistent left-aligned text, often accompanied by background music to enhance emotional connection. Japanese campaigns, on the other hand, show a more diverse approach in their use of text alignment and a balanced mix of real and illustrated visuals. The results suggest that motion graphics can effectively increase audience engagement and message retention, especially among younger viewers. The study concludes that well-designed visual campaigns have the potential to shape public perception and encourage more sustainable practices at the household level. It also highlights the need for future research into interactive and participatory media to deepen environmental education.